Management and outcome of placenta previa among women attending Khartoum maternity hospitals in Sudan - Handady, Siddig; Sakin, Hajar Hassan; Omer, Rania M. (International Journal of Medicine, 2015)
Background: The management of pregnancies complicated by placenta previa is best addressed in terms of the clinical setting: asymptomatic women, women who are actively bleeding and women who are stable after one or more episodes of active bleeding.Objective: To assess the management and outcome of placenta previa.Methodology: It was cross-sectional and hospital-basedstudy implemented during a time period of six months (July – December 2012) in Khartoum maternity hospital, and a total of50 women presented with VB diagnosed as placenta previa were selected through convenience sampling method.Results: Only two patients were deliver vaginally and C/S was done for 48(96.0%). Regarding outcome 16(32.0%) of patients were developed bleeding, 5(10%) of patients were ended by hysterectomy, 2(4%) developed acute renal failure, one maternal death and 26(52.0%) of patients were without obvious complications.Conclusions: The majority of women were undergone C/S and about (90.0%) their placenta were completely separated, (4.0%) left inside and (6.0%) left partially.